R-Z. - Lutzeier, Peter Rolf (De Gruyter, 2018)
The 3-volume dictionary presents words in German that have opposed readings as part of their individual polysemy. Such an opposite meaning is, for an individual word, analogous to the common antonymy that exists between different words. The concept of opposite meaning is relatively unknown and, in contrast to synonym and anytonym dictionaries, there exists no dictionary of opposite meanings for any language. In this sense, the current work is an innovation and will be of great interest to laypersons with an interest in language as well as to experts in the field. Dictionary of all words in the.